2001
DOI: 10.1093/emboj/20.8.2028
|View full text |Cite
|
Sign up to set email alerts
|

MOT1-catalyzed TBP-DNA disruption: uncoupling DNA conformational change and role of upstream DNA

Abstract: SNF2/SWI2-related ATPases employ ATP hydrolysis to disrupt protein±DNA interactions, but how ATP hydrolysis is coupled to disruption is not understood. Here we examine the mechanism of action of MOT1, a yeast SNF2/SWI2-related ATPase that uses ATP hydrolysis to remove TATA binding protein (TBP) from DNA. MOT1 function requires a 17 bp DNÀ handle' upstream of the TATA box, which must be double stranded. Remarkably, MOT1-catalyzed disruption of TBP±DNA does not appear to require DNA strand separation, DNA bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
94
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(106 citation statements)
references
References 51 publications
11
94
1
Order By: Relevance
“…Regardless, the binding of ATP is not sufficient for Mot1 to efficiently displace TBP from DNA. Consistent with published results (15,16,42) and Fig. 1B, addition of ATP allowed Mot1 to disrupt the TBP-DNA complex.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Regardless, the binding of ATP is not sufficient for Mot1 to efficiently displace TBP from DNA. Consistent with published results (15,16,42) and Fig. 1B, addition of ATP allowed Mot1 to disrupt the TBP-DNA complex.…”
Section: Resultssupporting
confidence: 92%
“…A template containing a 1-nt gap was employed to satisfy the requirement that there be at least 17 bp upstream of the TATA box for efficient Mot1-catalyzed TBP displacement while also allowing fluorophore placement (Fig. 1A) (42). We refer to this gap-containing duplex DNA template as "Gap DNA."…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Affinity of Mot1 for Gapped DNA Complexes-To investigate how the Mot1 ATPase utilizes DNA in the TBP-DNA dissociation reaction, functional studies focused on the DNA segment upstream of the TATA sequence, which had been shown in prior work to be important for Mot1 action (32,34). To determine the roles of DNA bases and backbone contacts in Mot1-mediated catalysis, we tested a series of DNA templates with 3-base gaps in either strand (Fig.…”
Section: Resultsmentioning
confidence: 99%